PENGARUH KUALITAS PRODUK, INFLUENCER MARKETING DAN CITRA MEREK TERHARAP KEPUTUSAN PEMBELIAN PRODUK MINUMAN HAUS INDONESIA - Septian Romendo Babeto Sinaga; Indra Fahrizal (Panorama Nusantara, 2025)
This study aims to examine the influence of product quality, influencer marketing, and brand image on the purchase decision of Haus Indonesia beverage products. This study uses a quantitative approach with multiple linear regression analysis method, which is processed using SPSS software version 25. The sampling technique used is purposive sampling, with the criteria of respondents who have purchased Haus Indonesia products at least twice. Data was obtained through the distribution of questionnaires to consumers in accordance with these criteria. The results of the study show that product quality, influencer marketing, and brand image have a significant effect on purchase decisions. Of the three variables, brand image is the most dominant factor in influencing consumer decisions, followed by product quality, and then influencer marketing. These findings underscore the importance of building a strong brand image, maintaining product quality, and implementing targeted influencer marketing strategies to improve consumer purchasing decisions.